Analisis Yuridis Perlindungan Hukum terhadap Hak Pekerja atas Tunjangan dan Upah yang Menunggak - Kaniko Dyon Geraldi; Gunardi Lie (PT. Hasba Edukasi Mandiri, 2026)
This research is motivated by the widespread violations of workers' rights regarding benefits and wages, which are frequently suspended or unpaid by companies due to the weak bargaining position of employees. Legally, an employment relationship obligates employers to fulfill the right to a decent living through wage components and allowances. The problem formulation in this study focuses on the legal protection provided to workers against the arrears of benefits and wages within the regulatory framework post-Reform. The research method employed is normative legal research using a statutory approach and a conceptual approach, utilizing primary, secondary, and tertiary legal materials.The results indicate that legal protection for wages and benefits has been reinforced through Article 88A of the Job Creation Law and the Manpower Law, which mandates employers to pay wages according to the agreed-upon terms. Violations regarding these components, including arrears in Social Security (BPJS Ketenagakerjaan) contributions, constitute not only a breach of contract but are also subject to administrative and criminal sanctions, with a maximum of 8 years imprisonment under the BPJS Law. However, the effectiveness of law enforcement is still hindered by passive labor inspection functions and the lengthy litigation process in the Industrial Relations Court. In conclusion, while the regulatory instruments are sufficiently robust, more active and consistent government oversight and firm enforcement of sanctions are required. It is recommended to strengthen the supervisory function and simplify dispute resolution mechanisms to ensure that workers' normative rights are fully protected for the sake of creating harmonious and fair industrial relations.